Enhanced metal assisted etching method for high aspect ratio microstructures: Applications in silicon micropillar array solar cells. (December 2019) - Baytemir, Gulsen; Ciftpinar, E. Hande; Turan, Rasit
Highlights: Radial junction for solar cells shortens the path length of the carriers. High density array micropillars allow carrier collection in the radial direction. High aspect ratio Si micropillars were fabricated by MAE through photolithography. EtOH-containing MAE solution with increased HF concentration forms smooth structures. 17.26% efficient radial juction solar cell with smooth micropillars was fabricated. Abstract: A solar cell device, fabricated on high density array cylindrical pillars, enables photogenerated carrier collection in the radial direction, thus shortening the path length of the carriers reaching the junction. It also provides advantages over conventional planar junction solar cells, such as reduced surface reflectance and enhanced light trapping. In this study, highly ordered Si micropillars were fabricated by photolithography and metal assisted etching (MAE) methods. It is shown that the use of ethanol as a solvent during the etching process and increasing HF concentration in the MAE solution both improve the quality of the surfaces of the pillars. Micropillars with smooth sidewalls and a high aspect ratio were obtained in this way. Solar cells with a radial junction were then fabricated on these micropillars. Standard doping, SiO2 /SiNx passivation, and metallisation steps were carried out for the fabrication of solar cells with different micropillar lengths. A significant decrease in reflectance values was observed as the micropillar length increased, as expected. Solar cell short circuit current density (Jsc ) and efficiency (η) of the solar cells tended to increase with micropillar length up to 11.5 µm and then decrease due to increased surface recombination. The maximum efficiency achieved in this study is 17.26%.